Difficult-to-treat psoriatic arthritis (D2T PsA): a scoping literature review informing a GRAPPA research project - Philip J Mease; Fabian Proft; Murat Torgutalp; Shikha Singla; Andre Ribeiro (RMD Open)
Background Psoriatic arthritis (PsA) is a multifaceted condition with a broad spectrum of manifestations and a range of associated comorbidities. A notable segment of patients with PsA remains resistant to even advanced therapeutic interventions. This resistance stems from myriad causes, including inflammatory and non-inflammatory factors.Objectives To collate and critically assess the various definitions and criteria of difficult-to-treat (D2T PsA present in the literature.Methods Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, we conducted a scoping review in July 2023, searching PubMed, American College of Rheumatology Convergence 2022, European Alliance of Associations for Rheumatology Congress 2023, Google Scholar and cited articles. Selection was made by two independent authors using Rayyan software, and conflicts were adjudicated by a third author. Eligibility criteria for PubMed focused on all article designs that were written in English, with full-text available, from the past decade, excluding only those not defining D2T PsA or targeting other populations.Results From the 565 references sourced, 15 studies were analysed, revealing considerable variations in defining both ‘active disease’ and ‘resistant PsA’, which was most often termed ‘D2T’ PsA.Conclusion The definitions and criteria for D2T PsA and for ‘active disease’ are notably heterogeneous, with considerable variation across sources. The ongoing Group for Research and Assessment of Psoriasis and Psoriatic Arthritis initiative stands to bridge these definitional gaps and aims to provide guidance for clinicians and illuminate a path for pharmaceuticals and regulatory agencies to follow.